Pengaruh Terapi Musik Terhadap Penurunan Kecemasan Pada Pasien Yang Menjalani Hemodialisa Dengan Gagal Ginjal Kronik - Budi Sanjaya; Yanti Cahyati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Chronic renal failure is the final failure stage where the nephrons cannot maintain their function. This disease contributes to the world's disease burden with a mortality rate of 850,000 people per year according to WHO. This kidney failure is followed by the high prevalence of patients undergoing hemodialysis which can interfere with the patient's physical and physiological condition. Some studies say that music therapy in kidney failure patients undergoing hemodialysis can reduce the anxiety level of patients undergoing hemodialysis. Methods: This research is a literature review of 3 articles. Articles searched through Google Scholar and Pubmed are searched according to keywords. for the nation with the keywords music therapy, anxiety, chronic kidney failure, and hemodialysis. Then for international articles, researchers determined the keywords music therapy, anxiety, chronic renal failure, and hemodialysis, and 3 articles that met the inclusion and exclusion criteria were selected. Results: The results of a review of 3 articles state that there is an effect of music therapy on reducing anxiety in patients undergoing hemodialysis with kidney failure. Discussion: There is a correlation between various studies related to the effect of reducing anxiety in patients undergoing hemodialysis with kidney failure. Conclusion: There is an effect of music therapy on reducing anxiety in patients undergoing hemodialysis with kidney failure and music therapy. This therapy is good to continue to be developed.